Analisis Pembelajaran Ilmu Balaghah di Madrasah Aliyah Muhammadiyah 08 Takerharjo Solokuro Lamongan - Nuzula, Ulfa Nur Simaa; Ammar, Farikh Marzuki (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2024)
Balaghoh science is the study of the implied meaning of an Arabic expression. The type of research used in this research is qualitative research with data collection techniques using observation, interviews and documentation. The subjects in this study were Balaghah subject teachers and 10th grade students at Madrasah Aliyah Muhammadiyah 08 Takerharjo. The purpose of this research is to find out the implementation of Balaghah learning, supporting and inhibiting factors, as well as solutions to the implementation of Balaghah learning at Madrasah Aliyah Muhammadiyah 08 Takerharjo. From the results of this study it can be concluded that the implementation of Balaghah learning is carried out by explaining the material to students and opening a question and answer session. The supporting factor for implementing the learning of Balaghah Science at Madrasah Aliyah Muhammadiyah 08 Takerharjo is because Balaghah Science is related to Arabic. The inhibiting factor for the implementation of learning Balaghah is that students are less interested in learning the sciences of the sciences. From the presence of inhibiting factors, there is a solution in the form of input from students for Balaghah Science subject teachers to improve their learning techniques so that students easily understand the material well. namely: the teacher reads the book followed by explaining the material from the chapter that has been read, then the teacher gives directions to students to practice reading the book Balahah and practice writing balaghah phrases in Arabic on the blackboard.